2022
DOI: 10.3390/pharmaceutics14101997
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Studies of Graphene for Management of Dental Caries and Periodontal Disease: A Concise Review

Abstract: Graphene is a single-layer two-dimensional carbon-based nanomaterial. It presents as a thin and strong material that has attracted many researchers’ attention. This study provides a concise review of the potential application of graphene materials in caries and periodontal disease management. Pristine or functionalized graphene and its derivatives exhibit favorable physicochemical, mechanical, and morphological properties applicable to biomedical applications. They can be activated and functionalized with meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 148 publications
0
10
0
Order By: Relevance
“…The antibacterial properties of graphene-based material against Streptococcus mutans are utilized by various dental materials to prevent biofilm formation and reduce demineralization and caries development. [ 88 89 ]…”
Section: Application Of Graphene and Its Derivatives In Dentistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial properties of graphene-based material against Streptococcus mutans are utilized by various dental materials to prevent biofilm formation and reduce demineralization and caries development. [ 88 89 ]…”
Section: Application Of Graphene and Its Derivatives In Dentistrymentioning
confidence: 99%
“…Periodontal pathogens can be suppressed by graphene and its derivative to control infection and prevent tissue destruction. [ 15 88 ] Several research concluded that graphene-based materials are highly effective against P. gingivalis ,[ 51 55 93 ] the leading bacteria responsible for periodontal disease. [ 94 ] Additionally, graphene derivatives can be utilized for guided tissue and bone regeneration.…”
Section: Application Of Graphene and Its Derivatives In Dentistrymentioning
confidence: 99%
“…Graphene is a single flat sheet of carbon-based nanomaterial with an ideal two-dimensional (2D) structure [ 32 ]. Unfortunately, it is not easy to synthesise large-scale graphene.…”
Section: Graphene-based Materialsmentioning
confidence: 99%
“…Therefore, derivatives of graphene, such as graphene oxide (GO) and reduced graphene oxide (rGO), have been introduced because they are easier to produce [ 105 ]. Graphene and its derivatives have many applications in science and technology, including dentistry [ 32 , 106 ]. For caries management, graphene-based materials have anti-cariogenic pathogen capacities [ 107 ] and mineralising properties [ 108 ].…”
Section: Graphene-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation